Pneumococcal septic shock after neonatal respiratory syncytial virus bronchiolitis: A case report and literature review - Di Caprio, Antonella; Coccolini, Elena; Zagni, Paola; Vaccina, Eleonora; Lucaccioni, Laura; Lugli, Licia; Iughetti, Lorenzo; Berardi, Alberto (Acta Biomedica Atenei Parmensis, 2021)
Background: Bronchiolitis is a common cause of hospitalisation of infants less than a year old, with most infants recovering without complications. Respiratory syncytial virus (RSV) is a leading cause of bronchiolitis. Antimicrobial stewardship programmes do not recommend antibiotics for viral infections in neonates unless documented evidence of secondary bacterial infection is present. Case report: We present the case of a 7-day-old infant admitted to hospital with chest retractions and fever. The baby was hospitalised, empirical antibiotic therapy was administered, and non-invasive ventilation was started. When the viral aetiology was identified and clinical conditions improved, antibiotics were discontinued. However, after 48 hours, the newborn's condition worsened because of pneumococcal septic shock. Intravenous fluids, catecholamine support, and wide-spectrum antibiotics were administered. Non-invasive ventilation was re-started and continued until the full recovery. Conclusions: There is increasing evidence that RSV and S. pneumoniae co-infect and interact with each other, thus increasing respiratory diseases' severity. We provide a brief overview of the main international guidelines for managing bronchiolitis. Guidelines suggest avoidance of antibiotics use when the diagnosis of viral bronchiolitis is confirmed. We discuss the uncertainties regarding antibiotic use, especially in younger infants, who are more exposed to risks of bacterial superinfection.